Multi‐Valent Group 14 Chalcogenide Architectures from Ionic Liquids: 0D‐[Cs@SnII4(GeIV4Se10)4]7− and 2D‐[SnII(GeIV4Se10)]2−. Issue 46 (21st June 2018) - Santner, Silke; Wolff, Alexander; Ruck, Michael; Dehnen, Stefanie
Abstract: In order to explore if and how salts comprising polycations and salts comprising polyanions might interact, the [AlBr4 ] − salt of the [Pt@Bi10 ] 4+ cluster cation was added to the reaction mixture for the synthesis of the supersphere cluster anion [Ge24 Sn36 Se132 ] 24− from Cs4 [Ge4 Se10 ]⋅ H2 O and SnCl4 ⋅ 5 H2 O under ionothermal conditions at 120 °C. Indeed, the reaction yields two new compounds, depending on the cation of the used ionic liquid. Apparently, the polycation is not retained under the given conditions, but it acts as a reductant affording Sn II . In a (C4 C1 C1 im) + ‐based ionic liquid mixture, a unique supertetrahedral anion is obtained that embeds a Cs + cation, 0D‐[Cs@Sn II 4 (Ge IV 4 Se10 )4 ] 7− , while (C4 C1 im) + cations stabilize an unprecedented ternary layered anion, 2D‐[Sn II (Ge IV 4 Se10 )] 2− . Test reactions with common sources of Sn II did not afford the new compounds, indicating the necessity of an in situ reduction, for which the polycation seems appropriate. Abstract : Sweet little fourteen : A novel supertetrahedral architecture is found in 0D‐[Cs@Sn II 4 (Ge IV 4 Se10 )4 ] 7− (in 1 ), upon ionothermal reaction of Cs4 [Ge4 Se10 ]⋅ H2 O and SnCl4 ⋅ 5 H2 O with [Pt@Bi10 ][AlBr4 ]4 in (C4 C1 C1 im)([BF4 ], Cl) at 120 °C. The use (C4 C1 im)([BF4 ], Cl), in contrast, yields an unprecedented layered structure, 2D‐[Sn II (Ge IV 4 Se10 )] 2− (in 2 ). While [Pt@Bi10 ] 4+ is not retained under the given conditions, it acts as a reductant affording Sn II, which cannot be easily replaced with other sources of Sn II . The Sn atoms in 1 stabilize an interstitial Cs + cation (see Figure).